2012
DOI: 10.1002/joc.3442
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of monthly average daily solar radiation from measured meteorological data in Yangtze River Basin in China

Abstract: Solar radiation is the principal and fundamental energy for many physical, chemical and biological processes. However, it is measured at a very limited number of meteorological stations in the world. Estimation of solar radiation from measured meteorological variables offers an important alternative in absence of measured solar radiation. In this work, 20 developed models using measured meteorological variables are explored to estimate monthly average daily solar radiation at 13 stations in Yangtze River Basin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 44 publications
5
39
1
Order By: Relevance
“…Among these methods, the empirical model using observed meteorological data is attractive for the good performances and data availability [8]. Ångström-Prescott (A-P) model [9] based on sunshine duration, Hargreaves-Samani (H-S) model (1982) [6] and Bristow-Campbell (B-C) model (1984) [10] based on diurnal temperature ranges are three simple but useful empirical models that have been widely used to estimate solar radiation in many regions around the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these methods, the empirical model using observed meteorological data is attractive for the good performances and data availability [8]. Ångström-Prescott (A-P) model [9] based on sunshine duration, Hargreaves-Samani (H-S) model (1982) [6] and Bristow-Campbell (B-C) model (1984) [10] based on diurnal temperature ranges are three simple but useful empirical models that have been widely used to estimate solar radiation in many regions around the world.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies show that those modifications are not always showing any advantages comparing to the original equation [13,14]. The H-S model proposed by Hargreaves and Samani has also been modified with different equations in various places but the improvements of those modifications are various from different regions [8] and the modified versions sometimes even perform worse [15]. Therefore, calibration of the parameters in the original model is still a useful method for good precision comparing to modification of the current models.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the cost of measuring equipment and its difficult maintenance and calibration, lack of sufficient solar radiation data has been reported in many countries like USA [4,5], United Kingdom [6], Egypt [7], India [8], France [9], Greece [10], Italy [11] and China [12][13][14]. On the contrary, air temperature is routinely measured at most meteorological stations.…”
Section: Introductionmentioning
confidence: 99%
“…Hargreaves and Samani [15] proposed a model (H-S model) using air temperature range, several modified versions were developed and validated in many places around the world [17][18][19][20]. Although some authors claimed that their new versions outperformed the original model, this may not always be the cases in many studies even when other commonly measured meteorological variables are taken into account [4,13,21,22]. Bristow and Campbell [16] developed a model (B-C model) as exponential function of temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are based on empirical modelling related to variables such as temperature Bristow and Campbell, 1984;Donatelli and Campbell, 1998;Goodin et al,1999;Mahmood and Hubbard, 2002;Benghanem and Mellit, 2014), sunshine duration ( Angstrom, 1924;Prescott, 1940;Al-Mostafa et al, 2014;Despotovic et al, 2015;Lockart et al, 2015;Teke et al, 2015), rainfall ( McCaskill, 1990;Liu and Scott, 2001;Chen et al, 2006;Wu et al, 2007;Kirmani et al, 2015), cloudiness ( Supit and van Kappel, 1998;Gu et al, 2001;Badescu, 2002), elevation (Allen, 1995;Winslow et al, 2001;Annandale et al, 2002), humidity (Gu et al, 2001;Chen et al, 2006;Almorox et al, 2011;Li et al, 2013;Antonanzas-Torres et al, 2013;Li et al, 2015) and latitude (Toğrul and Onat, 1999;Skeiker, 2006). Several studies have shown that the best performing models use sunshine duration data, followed by those utilizing cloudiness and then temperature data (Bakirci, 2009;Chen and Li, 2013). However, sunshine and cloudiness data are not available at most meteorological stations.…”
Section: Estimation Of Extraterrestrial Radiationmentioning
confidence: 99%